2010
DOI: 10.1101/cshperspect.a002170
|View full text |Cite
|
Sign up to set email alerts
|

From Self-Assembled Vesicles to Protocells

Abstract: Self-assembled vesicles are essential components of primitive cells. We review the importance of vesicles during the origins of life, fundamental thermodynamics and kinetics of self-assembly, and experimental models of simple vesicles, focusing on prebiotically plausible fatty acids and their derivatives. We review recent work on interactions of simple vesicles with RNA and other studies of the transition from vesicles to protocells. Finally we discuss current challenges in understanding the biophysics of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
188
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(198 citation statements)
references
References 89 publications
(88 reference statements)
1
188
0
3
Order By: Relevance
“…Thus, life's abiotic origin is not just a chicken-and-egg problem, but also a yolk-and-shell problem. Besides the RNA-world, there is in fact a lipid-world theory that argues for the early appearance of vesicles and protocells (90,91). Venter and coworkers' Mycoplasma laboratorium experiment (92) or Michael Crichton's Jurassic Park fiction both require placing remodeled or renewed DNAs into a preexisting cell.…”
Section: The Originmentioning
confidence: 99%
“…Thus, life's abiotic origin is not just a chicken-and-egg problem, but also a yolk-and-shell problem. Besides the RNA-world, there is in fact a lipid-world theory that argues for the early appearance of vesicles and protocells (90,91). Venter and coworkers' Mycoplasma laboratorium experiment (92) or Michael Crichton's Jurassic Park fiction both require placing remodeled or renewed DNAs into a preexisting cell.…”
Section: The Originmentioning
confidence: 99%
“…The first membranes were most probably singlechain fatty acids 143,[145][146][147][148] . Once simple amphiphilic molecules were present, spontaneous formation of vesicles became possible under specific circumstances 145,147,149 . Interestingly, spontaneous membrane assembly is also catalysed by certain mineral surfaces 150 , offering a conceptual bridge between the surface bound and encapsulated replicators in the evolution of the RNA world.…”
Section: Ii/3 Active Compartmentalizationmentioning
confidence: 99%
“…Moreover, there are RNA molecules that catalyse amphiphiles formation. Laboratory experiments confirmed that amphiphilic membranes can self-assembly spontaneously in prebiotic environments (Chen and Walde, 2010). Minerals and specific ions that existed on the primordial Earth can speed up the process of formation of membranes.…”
Section: 2mentioning
confidence: 89%